AB0778 Vespa Study: Association Between Spondyloarthritis and Hidradenitis Suppurativa. (9th June 2015) - Fauconier, M.; Reguiai, Z.; Colosio, A.; Barbe, C.; Eschard, J.P.; Salmon, J.H.; Direz, G.
Abstract : Background: Hidradenitis suppurative (HS) is a chronic inflammatory disease that results in abcesses, keloids and fistula. If the association between Crohn's disease (CD) and HS has already been esthablished, few reports have also described a possible association between HS and spondyloarthritis (SpA). Objectives: To study the association between HS and SpA. Methods: A monocentric, cross-sectional study was realised; 50 patients with HS and 50 volunteers without dermatologic affection, matched on age and gender, were enrolled. They had a clinical examination, HLA-B27 research and underwent a sacro-iliac MRI. Afterward, patients were listed according to the ASAS criteria for SpA. Results: 39 patients with HS disease and 50 control patients were analyzed. In HS patients (mean age 36±11.3; 70% women) 11 of them (28%) fulfilled the ASAS criteria, although 4 of them were already known. Only 1 patient (2%) fulfilled those criteria in the control group. Axial spondyloarthritis was the most common form of SpA observed with 9 patients of 11. There was no significant association with HLA B27 haplotype. After adjustment for age, gender and personal or familial history of psoriasis or inflammatory bowel disease, we proved that HS is an independent risk factor for SpA (OR 19.5; 95% CI [1.7;216]). Conclusions: We proved that HS disease is statistically associated with SpA. We think that HS patients, especially men, who present osteoarticular symptoms have to be monitored for spondyloarthritis research. Disclosure of Interest: None declared